Population dynamics of Brachionus calyciflorus driven by the associated natural bacterioplankton - Zhang, Yongzhi; Feng, Sen; Zhu, Lingyun; Li, Meng; Xiang, Xianling (Frontiers in Microbiology, 2023)
Zooplankton provides bacteria with a complex microhabitat richen in organic and inorganic nutrients, and the bacteria community also changes the physiochemical conditions for zooplankton, where the symbiotic relationship between them plays an important role in the nutrient cycle. However, there are few studies on the effect of associated bacteria on the population dynamics of rotifers. In order to make clear their relationships, we reconstructed the associated bacterial community in Brachionus calyciflorus culture, and examined the life history and population growth parameters, and analyzed the diversity and community composition of the associated bacteria at different growth stages of B. calyciflorus. The results showed that the addition of bacteria from natural water can promote the population growth and asexual reproduction of B. calyciflorus, but has no significant effect on sexual reproduction, exhibited by the improvement of its life expectancy at hatching, net reproduction rates and intrinsic growth rate, no significant effects on the generation time and mixis ratio of offspring. It was found that the B. calyciflorus-associated bacterial community was mainly composed of Proteobacteria, Bacteroidota, Actinobacteriota, Cyanobacteria and Firmicutes. Through correlation network analysis, the members of Burkholderiales, Pseudomonadales, Micrococcales, Caulobacterales and Bifidobacteriales were the keystone taxa of B. calyciflorus-associated bacteria. In addition, the relative abundance of some specific bacteria strains increased as the population density of B. calyciflorus increased, such as Hydrogenophaga, Acidovorax, Flavobacterium, Rheinheimera, Novosphingobium and Limnobacter, and their relative abundance increased obviously during the slow and exponential phases of population growth. Meanwhile, the relative abundance of adverse taxa (such as Elizabethkingia and Rickettsiales) decreased significantly with the increase in rotifer population density. In conclusion, the closely associated bacteria are not sufficient for the best growth of B. calyciflorus, and external bacterioplankton is necessary. Furthermore, the function of keystone and rare taxa is necessary for further exploration. The investigation of the symbiotic relationship between zooplankton-associated bacterial and bacterioplankton communities will contribute to monitoring their roles in freshwater ecosystems, and regulate the population dynamics of the micro-food web.